PERUBAHAN BENTUK NOMINA DALAM KONTRUKSI KALIMAT BAHASA NIAS UTARA DIALEK TENGAH DI AMANDRAYA - Darna Kristal Laia (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research was motivated by the change in the form of nouns in sentence construction, especially in Hilimeara Village, Amandraya District. This research aims to describe changes in the form of basic nouns in the North Nias language, the central dialect of Amandraya. The approach used in this research is qualitative with a content analysis method. The data source in this research is primary data and the informants in this research are three people in Hilimaera Village, Amandraya District, using documentation and interviews with criteria (understanding Nias language and understanding nouns), according to the context and topic. The data analysis techniques in this research are data reduction, data presentation and conclusions/verification. The findings of this research indicate that there is a change in the construction of nouns used in the North Nias language, the central dialect of Amandraya. This change in noun form occurs when the interrogative sentence changes form to a telling sentence and when the telling sentence changes form to an interrogative sentence. The researcher's suggestion is that the findings of this research can be used as comparison material for future researchers and it is hoped that it can provide additional new insights in the field of Indonesian literary language, especially the form of changes in the construction of basic nouns.